2010
DOI: 10.1096/fj.09-150995
|View full text |Cite
|
Sign up to set email alerts
|

ISX is a retinoic acid‐sensitive gatekeeper that controls intestinal β,β‐carotene absorption and vitamin A production

Abstract: The uptake of dietary lipids from the small intestine is a complex process that depends on the activities of specific membrane receptors with yet unknown regulatory mechanisms. Using both mouse models and human cell lines, we show here that intestinal lipid absorption by the scavenger receptor class B type 1 (SR-BI) is subject to control by retinoid signaling. Retinoic acid via retinoic acid receptors induced expression of the intestinal transcription factor ISX. ISX then repressed the expression of SR-B1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
213
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(222 citation statements)
references
References 40 publications
3
213
1
Order By: Relevance
“…intestinal carotenoid absorption is greatly attenuated by dietary retinoids (Lobo et al, 2010b). This characteristic explains why Bcdo2 deficiency does not result in similar effects during mouse embryogenesis .…”
Section: Research Article Bcdo2 In Embryonic Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…intestinal carotenoid absorption is greatly attenuated by dietary retinoids (Lobo et al, 2010b). This characteristic explains why Bcdo2 deficiency does not result in similar effects during mouse embryogenesis .…”
Section: Research Article Bcdo2 In Embryonic Developmentmentioning
confidence: 99%
“…Rodents such as mice display low to undetectable levels of these compounds in blood and tissues (Hessel et al, 2007;Amengual et al, 2011), indicating that they have developed mechanisms to prevent carotenoid accumulation. Indeed, recent research revealed that intestinal carotenoid absorption is under negative-feedback regulation by vitamin A (Lobo et al, 2010b) and that non-proretinoid carotenoids are rapidly metabolized by BCDO2 (Ford et al, 2010;Amengual et al, 2011). By contrast, many mammals, including humans, and oviparous vertebrates, such as birds and fish, have significant levels of carotenoids in blood and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…ISX is a gut-specific transcription factor that is induced in intestinal cells by RA via RAR and functions to limit intestinal beta-carotene absorption and conversion to vitamin A through its effects on gene expression. 43 CYP26a1 is a RA hydroxylase that is transcriptionally induced by RA in a RAR-dependent manner. 44 ISX mRNA levels in intestine and CYP26a1 mRNA levels in liver and iWAT were higher in the RE rats than in the control rats (Figures 2a-c), indicating increased RA-mediated transcriptional responses in tissues of RE-treated animals.…”
Section: Other Determinationsmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] Scavenger receptor class B type 1 (SR-B1) might be a major receptor in the facilitated diffusion in Caco-2 cells, considering the results of studies using their antibodies and siRNAs. 22,25) In SR-B1 knockout mice, the efficiency of -carotene absorption was remarkably reduced, though not fully inhibited.…”
mentioning
confidence: 99%